2019
DOI: 10.1093/neuros/nyz485
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy in DAWN- and DEFUSE-3-Ineligible Patients: A Subgroup Analysis From the BEST Prospective Cohort Study

Abstract: BACKGROUND Because of the overwhelming benefit of thrombectomy for highly selected trial patients with large vessel occlusion (LVO), some trial-ineligible patients are being treated in practice. OBJECTIVE To determine the safety and efficacy of thrombectomy in DAWN/DEFUSE-3-ineligible patients. METHODS Using a multicenter prospective observational study of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
4
15
0
1
Order By: Relevance
“…This confirms observations made in patients who present in the early window, and corroborates recently published findings in one cohort treated in the extended window . Whether selected patients from this cohort still derive an overall benefit from thrombectomy (versus medical management alone) deserves further investigation and is being reported separately . Our findings emphasize the critical importance of reviewing the noncontrast CT before selecting patients for thrombectomy, even in the presence of favorable perfusion imaging profiles.…”
Section: Discussionsupporting
confidence: 90%
“…This confirms observations made in patients who present in the early window, and corroborates recently published findings in one cohort treated in the extended window . Whether selected patients from this cohort still derive an overall benefit from thrombectomy (versus medical management alone) deserves further investigation and is being reported separately . Our findings emphasize the critical importance of reviewing the noncontrast CT before selecting patients for thrombectomy, even in the presence of favorable perfusion imaging profiles.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with a recent single-center analysis by Salam et al (n = 166) where good functional outcome occurred in 24% [17]. The BEST cohort [9], another real-life study, also found worse clinical results of trial-eligible patients when compared to the randomized studies, but these were more favorable than in our cohort (mRS 0-2 = 30%, 14/47); however, the estimated infarct core volumes in BEST were very small (6 ml [0-20]) [9]. A very high proportion of patients with a good clinical outcome (67%) was found in a Swiss study including 52 ET patients [7] but the majority of patients (71.1%) in this study had M2 occlusions, which are in general more often associated with a good clinical outcome [18].…”
Section: Prevalence and Outcomesupporting
confidence: 90%
“…The 25 participating centers reflect both primary and comprehensive stroke centers (12 university hospitals and 13 municipal hospitals). A detailed description of the GSR study design, obtained parameters, and main outcome data was recently published [9,10].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, the DAWN and DEFUSE-3 trials demonstrated that MT was successfully applicable up to 24 h after stroke onset (16)(17)(18). Further trials investigated borderline LVO patients, such as large ischemic cores or distal occlusions (19,20). The number of MT procedures is expected to increase further.…”
Section: Discussion Of Results For Clinical Practicementioning
confidence: 99%